Synthesis, physiochemical property and antimicrobial activity of novel quaternary ammonium salts - Xianrui Xie; Wei Cong; Feng Zhao; Hongjuan Li; Wenyu Xin; Guige Hou; Chunhua Wang (Taylor & Francis Group, 2018)
Twenty-four novel 5-phenyl-1,3,4-oxadiazole-2-thiol (POT) analogues, benzo[d]oxazole-2-thiol, benzo[d]thiazole-2-thiol and 5-methyl-1,3,4-thiadiazole-2-thiol-substituted N,N-bis(2-hydroxyethyl) quaternary ammonium salts (QAS) (5a-d, 6a-d, 7a-d, 10a-d, 13a-d, 16a-d) were prepared and characterised by FTIR, NMR and elemental analysis. Part of target compounds (5d, 6d, 7d, 10d, 13d, 16d) displayed potent antimicrobial effect against ten common pathogens (S. aureus, α-H-tococcus, β-H-tococcus, E. coli, P. aeruginosa, Proteus vulgaris, Canidia Albicans, Cytospora mandshurica, Physalospora piricola, Aspergillus niger) and had relatively low cytotoxity against two human cell lines (HaCat and LO2). TEM and SEM images of E. coli and S. aureus morphologies treated with 7d showed that the antibacterial mechanism might be the QAS fixing on cell wall surfaces and puncturing to result in the release of bacterial cytoplasm. This study provides new information of QAS, which could be used to design novel antimicrobial agents applied in clinic or agriculture.